2019
DOI: 10.3168/jds.2018-16092
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Genetic aspects of milk differential somatic cell count in Holstein cows: A preliminary analysis

Abstract: The aim of the present study was to assess genetic variation and heritability of a novel indicator of udder health, milk differential somatic cell count (DSCC), which represents the percentage of neutrophils plus lymphocytes in the total somatic cell count (SCC). Furthermore, we estimated genetic and phenotypic correlations of DSCC with other milk traits routinely measured in Italian Holstein cows. Besides DSCC, testday data included milk yield, composition traits (i.e., fat, protein, casein, and lactose perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 21 publications
(26 reference statements)
8
14
1
1
Order By: Relevance
“…The average DSCC ranged from 65.2% (Brown Swiss) to 66.6% (Holstein Friesian; Table 1). Mean DSCC of Holstein Friesian observed in the present study was slightly higher than the value (62.07%) reported by Bobbo et al (2019); the difference is likely related to the fact that, after an update of the software, DSCC values corresponding to SCC < 50,000 cells/mL were set to zero in the output of the instrument (data not included in the current study). As a consequence, the average values of SCC increased slightly (Table 1).…”
Section: Descriptive Statisticscontrasting
confidence: 84%
See 1 more Smart Citation
“…The average DSCC ranged from 65.2% (Brown Swiss) to 66.6% (Holstein Friesian; Table 1). Mean DSCC of Holstein Friesian observed in the present study was slightly higher than the value (62.07%) reported by Bobbo et al (2019); the difference is likely related to the fact that, after an update of the software, DSCC values corresponding to SCC < 50,000 cells/mL were set to zero in the output of the instrument (data not included in the current study). As a consequence, the average values of SCC increased slightly (Table 1).…”
Section: Descriptive Statisticscontrasting
confidence: 84%
“…Milk differential somatic cell count (DSCC) is a novel indicator of udder health and it represents the percentage of neutrophils plus lymphocytes in the total SCC; therefore, the percentage of macrophages can be calculated as 100 -DSCC (Damm et al, 2017). The genetic background of DSCC has been recently investigated by Bobbo et al (2019), who reported that this novel trait may be exploited in selection programs for mastitis resistance, as its heritability (0.08) was even higher than that of somatic cell score (SCS; 0.04). Moreover, information on the proportion of the different cell types in milk, in combination with total SCC, would represent a valuable asset for a more precise definition of udder health status (Pillai et al, 2001;Pilla et al, 2012;Pilla et al, 2013), and would help farmers make decisions to reduce the use of antimicrobials.…”
Section: Introductionmentioning
confidence: 99%
“…These three cell types play different roles in the immune response to mastitis and their proportion in milk varies according to the infection status of the mammary gland (Damm et al 2017). Bobbo et al (2019) demonstrated that differential somatic cell count (DSCC), which is the ratio of neutrophils plus lymphocytes to total SCC (Damm et al 2017), is potentially exploitable in breeding programmes aimed to reduce udder health problems. Furthermore, Zecconi et al (2019) established a correlation between DSCC and SCC, and defined the most accurate thresholds of DSCC to maximise the probability of correctly identifying mammary gland status in Italian Holsteins.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DSCC has been proposed as a useful biomarker in milk to indirectly identify mastitis, revealing inflammatory reactions also at low SCC [20], and being able to determine the stage of mastitis in combination with SCC [19]. Genetic aspects of DSCC have also been preliminarily investigated in Holstein cows [21], suggesting the consideration of DSCC in breeding programs for the enhancement of bovine resistance to mastitis.…”
Section: Introductionmentioning
confidence: 99%